Внешняя рихтовка кузовов автотранспорта с помощью электродинамических систем при прямом пропускании импульсного тока - Бондаренко, Александр Юрьевич; Финкельштейн, Владимир Борисович; Гаврилова, Татьяна Владимировна (НТУ "ХПИ", 2014)
В статье предложены принципиальные решения модельных конструкций электродинамических систем, принцип действия которых основан на силовом взаимодействии параллельных проводников с однонаправленными токами, позволяющими устранение вмятин в кузовах автомобилей. Продемонстрировано реальную работоспособность предложенного инструмента внешней магнитно-импульсной рихтовки конкретными вычислениями.

The paper proposes the fundamental solution of model structures electrodynamic systems, whose operation is based on the force interaction of parallel conductors with unidirectional currents, allowing the removal of dents in the body of car. Proposed design concept tool for removing dents with parallel connection of the conduction and a site of sheet metal with a dent is offered. Demonstrated the real efficiency of the proposed instrument of external magnetoimpuls straightening by concrete calculations.
External straightening basket of the motor transport by means of electro dynamic of the systems at direct drive pulsed current
Keywords: внешняя рихтовка; индукторная система; однонаправленный ток; external straightening; induction system; unidirectional current